Comprehensive Analysis of Shear Deformation Cytometry Based on Numerical Simulation Method - Jun Wang; Jiahe Chen; Wenlai Tang; Shu Zhu (Biosensors, 2025)
The deformability of cells reflects their capacity for shape changes under external forces; however, the systematic investigation of deformation-influencing factors remains conspicuously underdeveloped. In this work, by using an incompressible neo-Hookean viscoelastic solid model, coupled with the Kelvin–Voigt model, the effects of flow rate, fluid viscosity, cell diameter, and shear modulus on cell deformability were systematically calculated and simulated. Additionally, the relationship between cell deformability and relaxation time within a dissipative process was also simulated. The results indicate that cell deformation is positively correlated with flow rate, with an approximate linear relationship between the deformation index and flow velocity. Fluid viscosity also significantly affects cell deformation, as an approximate linear relationship with the deformation index is observed. Cell diameter has a more prominent impact on cell deformability than do flow rate or fluid viscosity, with the deformation index increasing more rapidly than the cell diameter. As the Young’s modulus increases, cell deformation decreases non-linearly. Cell deformation in the channel also gradually decreases with the increase in relaxation time. These findings enhance the understanding of cell biophysical characteristics and provide a basis for the precise control of cell deformation in deformability cytometry. This research holds significant implications for cell analysis-based animal health monitoring in the field of agriculture, as well as for other related areas.